A simple and reliable method for determination of optimum pH in coupled enzyme assays - Lee Bowman; Rachael Motamed; Paul Lee; Kadijah Aleem; Astha S Berawala; Katherine L Hayden; David J Bzik; Debasish Chattopadhyay (BioTechniques, 2020)
Determination of the optimum pH in a coupled enzyme assay poses significant challenges because altering the pH of the reaction mixture can affect the performance of both enzymes. Here, we demonstrate a simple and reliable method to determine the pH optimum for pyruvate kinase using the pyruvate kinase/lactate dehydrogenase coupled enzyme assay. This simple and reliable method can be broadly adapted to determine the pH optimum for various enzymes that are assayed using a coupled enzyme assay.